Investigation of additively manufactured rigid polymers for Soft Robots application using Powder Bed Fusion - Cerqueira, Mateus Santos de; Shigueoka, Marcelo Okada; Silva, Bruno Caetano Dos Santos; Silva, Lucas Cruz Da; Juliano, Diego Russo; Beal, Valter Estevão (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
Soft robots are commonly constructed by integrating different technologies or employing indirect manufacturing methods to create a manipulator model. The compliant characteristics of a soft manipulator can be achieved through its geometry and flexibility. This article discusses the development of two types of soft robots: one controlled using tendons and the other pneumatically actuated. A comparison was carried out to assess the structural deformation of compliant parts compared to solid parts. The experiment demonstrated the construction of a compliant component using non-soft material properties.